2020
DOI: 10.1080/19476337.2020.1794981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding of different forms of oregano (Origanum vulgare) on lamb meat burgers quality during the storage time

Abstract: The effect of adding different oregano formats (GO: ground; OEX: extract; OEO: essential oil; OLO: oleoresin) on quality of vacuum packaged lamb burgers, during 14 days, was evaluated by pH, colour (L*, a* and b*), lipid oxidation and microbial growth [Total Viable Count (TVC), Enterobacteriaceae, Pseudomonas spp. and Lactic acid bacteria (LAB)]. A control batch (without spice) was used. After 10 days of storage, there was a marked decrease of pH in all samples, OEX reached the lowest value. There was variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
(59 reference statements)
2
15
1
1
Order By: Relevance
“…Curiously, the decrease was especially strong in the samples seasoned with oleoresin, which reached the lowest values (<5.5). These results contrast with those found in our previous paper (Vergara et al, 2020), in which different forms of oregano were compared in this same meat matrix, since the addition of oregano oleoresin on lamb burgers caused the highest pH. For this reason, it could be stated that the effect caused by the format of a spice depends on the spice itself.…”
Section: Physicochemical Parameterscontrasting
confidence: 98%
See 3 more Smart Citations
“…Curiously, the decrease was especially strong in the samples seasoned with oleoresin, which reached the lowest values (<5.5). These results contrast with those found in our previous paper (Vergara et al, 2020), in which different forms of oregano were compared in this same meat matrix, since the addition of oregano oleoresin on lamb burgers caused the highest pH. For this reason, it could be stated that the effect caused by the format of a spice depends on the spice itself.…”
Section: Physicochemical Parameterscontrasting
confidence: 98%
“…Shahidi et al (1995) studied the antioxidant efficacy of several ground spices in minced pork and observed that rosemary ranked third after cloves and sage. In our study, TBARS values reached in samples with ground rosemary were similar to those found in our previous papers in lamb burgers spiced with powder of thyme or sage (Cózar et al, 2018) or with oregano (Vergara et al, 2020).…”
Section: Lipid Oxidationsupporting
confidence: 91%
See 2 more Smart Citations
“…Debido a esto, durante los últimos años se han llevado cabo multitud de estudios para contrarrestar y mejorar este aspecto de las hamburguesas. Algunos de estos, han examinado la adicción de antioxidantes para mantener sus propiedades durante el almacenamiento o para mejorar sus beneficios para la salud, como subproductos de tomate (García et al, 2009), subproductos de uva y aceituna (Andrés et al, 2017;Sáyago-Ayerdi et al, 2009) o aceite esencial (Pateiro et al, 2018), aceite de corteza de canela (Hussain et al, 2021), especias como orégano (Vergara et al, 2020) o la incorporación de fibra vegetal en hamburguesas (García et al, 2009;Hautrive et al, 2019). En este sentido, la carne de cordero de razas autóctonas (Merina) se considera un producto natural de extraordinarios atributos sensoriales y una mayor concentración de n-3 (Linares et al, 2007(Linares et al, , 2008 y su producción está ligada en gran medida al ecosistema dehesa de forma sostenible.…”
Section: Introductionunclassified